¿Son masculinos e inclusivos los denominados sustantivos masculinos inclusivos en español? A vueltas con el género gramatical - Devís Márquez, P. Pablo (Verbum – Analecta Neolatina, 2022)
This article sets out a critical reflection on the existence in Spanish of the so-called inclusive masculine nouns and of grammatical gender regarded as a mere inherent feature of nominal forms. This inherent feature, allegedly, allows to classify these nominal forms according to their agreement with determiners, modifiers and other agreement elements. Our proposal does not apply grammatical gender to the linguistic class of nouns (and pronouns), but to their designative possibilities. This means recognizing procedures for grammatical gender expression in Spanish other than agreement, not circumscribing gender distinctions to the usual masculine–feminine one anymore, and offering an alternative explanation of the so-called inclusive masculine nouns.